Termite Valkyries: Soldier-Like Alate Termites From the Cretaceous and Task Specialization in the Early Evolution of Isoptera - Jouault, Corentin; Engel, Michael S.; Huang, Diying; Berger, Juliette; Grandcolas, Philippe; Perkovsky, Evgeny E.; Legendre, Frédéric; Nel, André (Frontiers in Ecology and Evolution, 2022)
In several insect eusocial lineages, e.g., some aphids, thrips, ants, some stingless bees, and termites, task specialization is brought to its climax with a sterile soldier caste solely devoted to colony defense. In Isoptera, while the reproductives are defenseless, the soldiers have unique morpho-physiological specializations whose origin and evolution remain unresolved. Here we report on two instances of Cretaceous fossil termite reproductives belonging to different families (†Valkyritermes inopinatus gen. et sp. nov. and an unpublished specimen from the Crato Formation), with intriguing phragmotic soldier-like heads and functional wings. These individuals, herein called Valkyries, are the first termite reproductives known with defensive features and suggest that phragmosis arose at least in the Early Cretaceous. Valkyries resemble modern neotenic soldiers except for their complete wings. Their discovery supports the hypothesis that the division between reproductive (indicated by the winged condition of Valkyries) and defensive tasks (indicated by the phragmotic head) has not always been complete in termite history. We explore two alternative scenarios regarding the origin of Valkyries (i.e., relatively recent and convergent origins vs. plesiomorphic condition) and discuss how they might relate to the development of soldiers. We argue that, in both cases, Valkyries likely evolved to face external threats, a selective pressure that could also have favored the origin of soldiers from helpers. Valkyries highlight the developmental flexibility of termites and illustrate the tortuous paths that evolution may follow.